EFEKTIFITAS PEMBELAJARAN TEKNIK PASSING ATAS PERMAINAN BOLA VOLI DENGAN PENDEKATAN BERMAIN DALAM MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS VII (STUDI PADA SMP NEGERI 16 SURABAYA TAHUN PELAJARAN 2011/2012) - PUDJIHIDAJAT, DJOKO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Passing the ball is presenting or pass the ball to your opponent using your fingers or directly into the opponent's field, in addition to passing on the good it will affect on the game, but it is more pronounced in high-level games than the game lower. A player must master the basic skills of passing on to attack and transfer the game of volleyball. Passing on is one of the sub material developed in physical education for students of class VII-A SMP Negeri 16 Surabaya. Underlying issue is the learning passing on the students at Junior High School 16 Surabaya are ketidksesuaian applying learning methods to the characteristics of class VII-A so that the passing on of learning volleyball SKM has not met 70%. This is due to students' lack of focus in learning and passing on and the students lack the basics of good passing. Therefore, teachers implement a model of learning by playing approach in the hope students can master the technique of passing on the implementation of learning. This study uses PTK (Classroom Action Research) to determine the passing mastery learning. Other research subjects were students of class VII-A SMP Negeri 16 Surabaya totaling 38 students. Each learning cycle seen no improvement. Preliminary studies by 15.79% to 47% in the first cycle, and to 79% in the second cycle. SKM 70% as determined by the teacher can be achieved. So from the fact that researchers study found, it can be concluded that there is an influence model of learning by playing approach to improving learning outcomes in students passing the class VII-A SMP Negeri 16 Surabaya. Keywords : Passing over, volleyball, action research, the approach play.